2017
DOI: 10.4317/jced.54004
|View full text |Cite
|
Sign up to set email alerts
|

Direct oral anticoagulants and its implications in dentistry. A review of literature

Abstract: BackgroundFour novel direct oral anticoagulants (DOACs) named dabigatran, rivaroxaban, edoxaban and apixaban have been recently introduced to overcome some of the drawbacks of existing anticoagulants. They have less interactions and do not require routine monitoring. However, there is not enough scientific data about the protocol to apply in these patients on DOACs undergoing dental treatment. Thus is necessary to evaluate the potential bleeding risk of these drugs, the possibility of thromboembolic events occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 41 publications
(48 reference statements)
1
21
0
3
Order By: Relevance
“…Conversely, the majority of studies in the scientific literature has dogmatically reported the interruption or continuation of the DOACs, as if the choice was only determined by the bleeding risk assessment, instead of being based on a balance between hemorrhagic risks, in case of continuation, and thromboembolic risks, in case of interruption. The use of direct oral anti coagulants for the prevention of thromboembolic events has tremendously increased during the last few years [26], and many clinicians have to manage patients who are under treatment with such medications and who need oral surgery procedures. It can be assumed that patients under treatment with anticoagulants and in need of oral surgery procedures have a higher risk of bleeding events.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the majority of studies in the scientific literature has dogmatically reported the interruption or continuation of the DOACs, as if the choice was only determined by the bleeding risk assessment, instead of being based on a balance between hemorrhagic risks, in case of continuation, and thromboembolic risks, in case of interruption. The use of direct oral anti coagulants for the prevention of thromboembolic events has tremendously increased during the last few years [26], and many clinicians have to manage patients who are under treatment with such medications and who need oral surgery procedures. It can be assumed that patients under treatment with anticoagulants and in need of oral surgery procedures have a higher risk of bleeding events.…”
Section: Discussionmentioning
confidence: 99%
“…We find anticoagulants such as dabigatran, with renal elimination, contraindicated in severe renal impairment [ 1 , 4 ]. It presents a half-life of 12 to 17 h [ 5 , 7 ] and its peak concentration in plasma is reached 2–3 h after its administration [ 5 ]. It also presents an antidote: idarucizumab [ 4 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…It also presents an antidote: idarucizumab [ 4 , 8 ]. On the other hand, rivaroxaban presents a plasma half-life of 7 to 13 h [ 5 ], reaching its maximum peak after 2–4 h [ 5 , 7 ]. Its antidote is andexanet alfa [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations